Pro-Inflammatory Alterations of Circulating Monocytes in Latent Tuberculosis Infection. (19th November 2022) - Feria, Manuel G; Chang, Cecilia; Ticona, Eduardo; Moussa, Anissa; Zhang, Bin; Ballena, Isabel; Azañero, Ruben; Ticona, Cesar; De Cecco, Carlo N; Fichtenbaum, Carl J; O'Donnell, Robert E; La Rosa, Alberto; et al.
Abstract: Background: Latent tuberculosis infection (LTBI) has been associated with increased cardiovascular risk. We investigated the activation and pro-inflammatory profile of monocytes in individuals with LTBI and their association with coronary artery disease (CAD). Methods: Individuals 40–70 years old in Lima, Peru, underwent QuantiFERON-TB testing to define LTBI, completed a coronary computed tomography angiography to evaluate CAD, and provided blood for monocyte profiling using flow cytometry. Cells were stimulated with lipopolysaccharide to assess interleukin-6 (IL-6) and tumor necrosis factor (TNF)–α responses. Results: The clinical characteristics of the LTBI (n = 28) and non-LTBI (n = 41) groups were similar. All monocyte subsets from LTBI individuals exhibited higher mean fluorescence intensity (MFI) of CX3CR1 and CD36 compared with non-LTBI individuals. LTBI individuals had an increased proportion of nonclassical monocytes expressing IL-6 (44.9 vs 26.9; P = .014), TNF-α (62.3 vs 35.1; P = .014), and TNF-α + IL-6 + (43.2 vs 36.6; P = .042). Among LTBI individuals, CAD was associated with lower CX3CR1 MFI on classical monocytes and lower CD36 MFI across all monocyte subsets. In multivariable analyses, lower CD36 MFI on total monocytes ( b = −0.17; P = .002) and all subsets remained independently associated with CAD in LTBI. Conclusions: Individuals with LTBI have distinct monocyte alterations suggestive of an exacerbated inflammatory response and tissue migration. Whether these alterations contribute to cardiovascular disease pathogenesis warrants further investigation.